Cooperative Learning Model Type of Index Card Match Against Science Learning Outcomes in Elementary School - Zulherman (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of science learning outcomes by using the Cooperative Learning Model Index Card Match type in fourth-grade students of SDN Jatiwaringin III Pondok Gede in semester 2 of the 2018-2019 school year. The research method used is a quantitative method with a Posttest-Only Control Design research design. The sampling used in this study is the Non-Probability sampling technique, which is saturated sampling. In the validity test using Point Biserial Correlation as many as 50 questions. Data were analyzed using the normality requirements test using the Liliefors test obtained in the experimental class Lo 0.14 <Lcount 0.161, in the control class Lo 0.15 <LCount 0.161. Then it can be concluded that the data from the two groups are normally distributed. Furthermore, a homogeneity test using the homogeneity test of two independent variables with the F test obtained Fcount of 1.12 with Sx12 = 82.80 and Sx22 = 73.82 and Ftable = 1.85. Fcount (1.12) <Ftable (1.85) it can be concluded that the variance of the two groups is homogeneous. In the hypothesis test t-test was used obtained tcount = 3.824 with Sgab = 8.85 at a significance level of α 0.05 degrees of freedom (DK) = 58 for 2.002. Because tcount (3,824)> ttable (2,002). Then it can be concluded that Ho was rejected and H1 accepted. The data stated that there is a significant effect on learning by using the Cooperative Type Index Card Match model on the learning outcomes of Natural Sciences fourth-grade SDN Jatiwaringin III Pondok Gede (Indonesia).